Peningkatan Hasil Belajar Ilmu Pengetahuan Alam dan Sosial Menggunakan Model Problem Based Learning di Kelas V Sekolah Dasar Negeri 17 Batu Gadang, Kota Padang - Elfina Nainggolan; Yarisda Ningsih (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Student learning outcomes are still low, seen in the implementation process where teachers predominantly provide information on subject matter so that students are less active, only listening to what is conveyed, teachers have not developed varied learning models resulting in students being less interested in identifying problems, so that student learning outcomes are low. Classroom Action Research was carried out with a qualitative and quantitative approach, carried out in 4 stages of planning, implementation, observation, and reflection. Implemented in two cycles, cycle I 2x meetings, cycle II 1x meeting. Research data were obtained from the teaching module plan, learning implementation, and learning outcomes. The research subjects of teachers and students of grade V SD N 17 Batu Gadang Kota Padang amounted to 21 people, 8 boys and 13 girls. The results of the observation research on the teaching module in cycle I obtained 83.33% qualification (B), increasing in cycle II to 95.83% very good qualification (SB). Implementation in the teacher aspect in cycle I obtained an average of 82.14% qualification (B) increasing in cycle II to 96.42% qualification (SB). Implementation of the student aspect in cycle I obtained an average of 82.14% with qualification (B) increasing in cycle II to 96.42% with very good qualification (SB). Student learning outcomes in cycle I obtained an average value of 76.10 with qualification (C) increasing in cycle II to an average value of 89.23 with qualification (B). Thus, it can be concluded that the Probem Based Learning model can improve student learning outcomes in science learning in class V of SD N 17 Batu Gadang, Padang City.